Pengaruh Website Design, Customer Trust Dan Personalization terhadap Purchase Intention melalui Customer Satisfaction Pada E-commerce Shopee - Willy Pebriana Chandra Kirana; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami (STIE AMKOP, 2023)
The purpose of this study was to determine the effect of website design, customer trust, and personalization of purchase intentions on customer satisfaction at Shopee e-commerce. this research is quantitative. The population in this study were undergraduate students at Sarjanwiyata Tamansiswa University who shopped using e-commerce with a sample of 100 respondents. The sampling technique used a purposive sampling technique by filling out a questionnaire via the Google form. The analytical method uses validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, statistical t tests using the SPSS 26 program and Sobel tests using the free statistical calculator version 4.0. The results obtained show that website design has no effect on purchase intention, customer trust has no effect on purchase intention, personalization has a positive and significant effect on purchase intention. Likewise, website design has a positive and significant effect on customer satisfaction, customer trust has a positive and significant effect on customer satisfaction, personalization has a positive and significant effect on customer satisfaction, customer satisfaction is able to mediate website design, customer trust and personalization on purchase intentions. Keywords: Website Design, Customer Trust, Personalization, Customer Satisfaction, Purchase Intention